The sheet ,,Cuvântul Adevărului’’, a publication of the bishop from White Fortress - Ismail (Confluenţe Bibliologice, 2023)
The article presents information about the activity of the bishops of the diocesan of  Ismail - White Fortress  ,Policarp Maruşca and Antim Nica oriented towards the enlightenment of the people by editing the publication ,,Cuvântul adevărului” and the Bulletin of the Ismail White Fortress Episcopate , publications that cultivated love for the homeland and nation.
Keywords: periodicals